Can a negative destination image be improved through hosting a mega sports event?: the case of smart tourism city Pyeong Chang. Issue 1 (2nd January 2022) - Lee, Pam; Koo, Chulmo; Chung, Namho
ABSTRACT: Mega sports events have received increasing attention as a source of revenue and because they confer other economic benefits to the host cities, regions, and countries involved. The 2018 Winter Olympics in Pyeong Chang has drawn tremendous attention from the world for their remarkable outcome both on the side of athletics and politicians under the tension between North, and South Korea have escalated. This study examines the impact of Pyeong Chang Olympics on destination image to investigate how the negative issues shift to a positive destination image through hosting a mega sports event satisfaction and eventually its impact on intention to revisit. The results suggest that negative destination issues have no significant impact on destination satisfaction, whereas negative Olympic issues influence does and both Olympic and destination satisfactions influence destination image. This study introduces the concept of image transfer over the satisfaction process based on empirical evidence and enriches the understanding of the nature of destination image transfer.